(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the thickness distribution of thermoformed clear aligners according to tooth group and different locations on the same tooth. Materials and methods: An in vitro experimental study was conducted on 10 clear aligners thermoformed on a 3D-printed maxillary model. The thermoplastic material used was Zendura FLX with an initial thickness of 0.76 mm. Aligner thickness was measured using an electronic micrometer at five anatomical locations on the maxillary central incisor (R1) and canine (R3), including: incisal edge/cusp tip, center of the labial surface, labial cervical region, center of the palatal surface, and palatal cervical region. Data were analyzed using one-way ANOVA with Tukey HSD post hoc tests and paired t-tests. Results: The thermoforming process significantly reduced aligner thickness and produced a non-uniform thickness distribution across the dental arch. The mean thickness in the incisor region (344.23 ± 4.06 µm) was significantly lower than that in the canine region (408.97 ± 4.94 µm) (p < 0.001). Within each tooth, aligner thickness differed significantly among anatomical locations (p < 0.001). The labial cervical region was the thinnest area, while the incisal edge/cusp tip and palatal surface tended to be thicker. At most corresponding locations, aligners in the canine region were thicker than those in the incisor region. Conclusion: The thermoforming process reduces aligner thickness; however, the degree of reduction varies depending on the tooth region and location on the same tooth. Overall, aligners tend to become thinner from posterior to anterior, and within a tooth, the labial cervical region is the thinnest area.